Business Processes in the Transport and Logistics in Economic Operation of the Enterprise - PARKHOMENKO, V.; CHARYEVК. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
Because the transport and logistics system (TLS) of the business enterprise is exposed to obvious and hidden high risks for the owners, its business processes need effective management throughout the value added chain. The purpose of the article is to present theoretical and methodological justification of TLS operation at enterprise level from the perspective of integrated management of business processes involved in the transport and logistics services. The article focuses on elaborating and constructing a diagram of the three-vector approach to building up TLS in the business enterprise, based on the compliance with the regulatory norms (national and international regulatory framework, intramural regulations, compliance with contract terms), risk orientation (economic forecasting of TLS performance, optimization of TLS capacities, analysis of contracting parties operation, computerization of business processes, economic projecting and strategic management), and client orientation (high quality of the provided services, infrastructure improvements, free competition, effective marketing, rationalization of supply chains, provision of guarantees; price policy). It is proposed to group the key business processes involved in TLS by transport and logistics activities, with account to the activity specifics and size of the enterprise, terms of service delivery and other factors of value added creation. A set of indicators for performance assessment of TLS is constructed, classified in the following groups: quality of transport services, efficiency of freight transport, business indicators of diagnostics of the transport activities as a component of the logistics system, assessment of logistics rules, transport efficiency. These indicators will provide an effective tool for performance assessment of TLS at enterprise level.